Logic-Based Program Synthesis and Transformation 23rd International Symposium, LOPSTR 2013, Madrid, Spain, September 18-19, 2013, Revised Selected Papers - Gupta, Gopal; Peña, Ricardo (Theoretical Computer Science and General Issues,, 2014)
This book constitutes the thoroughly refereed post-conference proceedings of the 23rd International Symposium on Logic-Based Program Synthesis and Transformation, LOPSTR 2013, held in Madrid, Spain, in September 2013. The 13 revised full papers presented together with 2 invited talks were carefully reviewed and selected from 21 submissions during two rounds of reviewing and improvement. LOPSTR traditionally solicits papers in the areas of specification, synthesis, verification, transformation, analysis, optimization, composition, security, reuse, applications and tools, component-based software development, software architectures, agent-based software development, and program refinement.